Perceptions of senior phase teaching in implementing teaching and learning materials within Sepedi Home Language curriculum : a case of Tubatse Circuit, Sekhukhune East District, Limpopo Province, South Africa. - Nkgapele, Mokgadi Japhtalinah (My University, 2024)
This study aims to explore the perceptions of Senior Phase teachers in implementing teaching and learning materials within the Sepedi Home Language curriculum at Tubatse Circuit, Sekhukhune East District, Limpopo Province, South Africa. The quester-view approach was used to collect data in written and/or face-to-face forms. The study sampled three (3) teachers per three primary schools and three (3) Departmental Heads from the sampled schools. Data was analysed thematically following the inductive method. The study intended to find out why Senior-Phase teachers do not find it easy to implement the Sepedi Home Language curriculum, investigating the relevancy of the teaching and learning materials since they are developed from the guidelines of a second language and written in English rather than Sepedi.
Thesis (M. Ed. (Language Education)) -- University of Limpopo, 2024
Keywords: Teaching and learning materials; Curriculum development; Senior phase; Language policy; Vocabulary enrichment; Indigenous languages; Language transfer (language learning); Classroom learning centers; Curriculum planning; Northern Sotho language -- Study and teaching -- South Africa -- Limpopo